Attributes of top elite team-handball players - Massuca, L. M.; Fragoso, I.; Teles, J. (The Journal of Strength and Conditioning Research, 2014)
Researchers in the field of excellence in sport performance are becoming increasingly focused on the study of sport-specific characteristics and requirements. In accordance with this, the purposes of this study were (a) to examine the morphologic-, fitness-, handball-specific skills and psychological and "biosocial" differences between top elite and nontop elite team-handball players and (b) to investigate the extent to which they may be used to identify top elite team-handball players. One hundred sixty-seven adult male team-handball players were studied and divided in 2 groups: top elite (n = 41) and nontop elite (n = 126). Twenty-eight morphologic-, 9 fitness-, 1 handball-specific skills and 2 psychological-based and 2 "biosocial"-based attributes were used. Top elite and nontop elite groups were compared for each variable of interest using Student's t-test, and 5 logistic regression analyses were performed with the athlete's performance group (top elite or nontop elite) as the dependent variable and the variables of each category as predictors. The results showed that (a) body mass, waist girth, radiale-dactylion length, midstylion-dactylion length, and absolute muscle mass (morphologic model); (b) 30-m sprint time, countermovement jump height and average power, abdominal strength and the class of performance in the Yo-Yo Intermittent Endurance Test (fitness model); (c) offensive power (specific-skills model); (d) ego-based motivational orientation (psychological model); (e) socioeconomic status and the energy spent (for week) in handball activity (biosocial model); significantly (p < 0.05) contributed to predict the probability of an athlete to be a top elite team-handball player. Moreover, the fitness model exhibited higher percentages of correct classification (i.e., 91.5%) than all the other models did. This study provided (a) the rational to reduce the battery of tests for evaluation purposes, and (b) the initial step to work on building a multidisciplinary model to predict the probability of a handball athlete to be a top elite player.